Does N‐terminal Pro‐brain Type Natriuretic Peptide Predict Cardiac Complications After Hip Fracture Surgery?. Issue 6 (June 2017) - Ushirozako, Hiroki; Ohishi, Tsuyoshi; Fujita, Tomotada; Suzuki, Daisuke; Yamamoto, Kazufumi; Banno, Tomohiro; Takase, Hiroyuki; Matsuyama, Yukihiro
Abstract: Background: Elderly patients with hip fracture are at risk for cardiac complications. N‐terminal pro‐brain type natriuretic peptide (NT‐proBNP) has been shown to predict cardiac complications in surgical patients; however, to our knowledge, only two studies have evaluated the utility of this test in patients with hip fracture. We believe it is important to assess a more accurate cutoff value of NT‐proBNP with exclusion of patients with renal failure. Questions/Purposes: To assess the association between preoperative NT‐proBNP and cardiac complications after hip fracture surgery. Methods: We performed 450 surgical procedures in patients with hip fractures between January 2011 and December 2014. Exclusion criteria were renal dysfunction and inadequate laboratory tests. The final study population consisted of 328 patients (mean age, 83 years; 80% women). Preoperatively, measurement of NT‐proBNP level was performed. The primary endpoint was the occurrence of cardiac complications within 14 days after surgery based on a chart review. The predictive value of NT‐proBNP was assessed using multivariate logistic regression analysis, controlling for relevant confounding variables such as age, gender, body weight, and renal function; we also performed receiver operating characteristic (ROC) curve analysis. Postoperative cardiac complications were encountered in 7% of patients (24 of 328). Results: The median preoperative NT‐proBNP level was higher in patients with complications than in those without (1090 [interquartile range, 614‐3191 pg/mL] vs 283 pg/mL [interquartile range, 137‐507 pg/mL], p < 0.001). The cutoff level of NT‐proBNP determined by ROC curve analysis was 600 pg/mL, with a sensitivity, specificity, positive predictive value, and negative predictive value of 79%, 81%, 25%, and 98%, respectively, and the area under the ROC curve was 0.87 (95% CI, 0.80‐0.94; p < 0.001). After controlling for potentially relevant confounding variables, we found a preoperative NT‐proBNP greater than 600 pg/mL was associated with an increased risk of cardiac complications (odds ratio, 13; 95% CI, 4‐38; p < 0.001) compared with those with NT‐proBNP less than 600 pg/mL. Conclusions: Preoperative NT‐proBNP greater than 600 pg/mL is independently associated with postoperative cardiac complications in patients with hip fracture without renal dysfunction. NT‐proBNP measurement provides additional information and is clinically useful for predicting cardiac complications during the early phase after hip fracture surgery. Future studies might develop a simple index for prediction of postoperative cardiac complication including cutoff values of NT‐proBNP. Level of Evidence: Level III, diagnostic study.